Genetic and behavioral analysis of flagellar switch mutants of Salmonella typhimurium. - Magariyama, Y (1990)
At the interface between the sensory transduction system and the flagellar motor system of Salmonella typhimurium, the switch complex plays an important role in both sensory transduction and energy transduction. To examine the function of the switch complex, we isolated from 10 cheY mutants 500 pseudorevertants with a suppressor mutation in one of the three genes (fliG, fliM, and fliN) encoding the switch complex. Detailed mapping revealed that these suppressor mutations were localized to several segments of each switch gene, suggesting localization of functional sites on the switch complex. These switch mutations were introduced into the wild-type background and into a chemotaxis deletion background. Behavior of the pseudorevertants and their derivatives (1,500 strains in all) was observed by light microscopy. In the chemotaxis deletion background, about 70% of the switch mutants showed smooth swimming and the rest showed more or less tumbly swimming. There was some correlation between the mutational sites and the swimming patterns in the chemotaxis deletion background, suggesting that there is segregation of functional sites on the switch complex. The interaction of the switch complex with the chemotaxis protein, CheY, and the stochastic nature of switching in the absence of CheY are discussed.